Florida's Criminal Justice Workforce Research Information System, 1985-1996 ([Verlag nicht ermittelbar], 2000)
This project sought to prove that research files could be created through the extraction of personnel management systems data. There were five goals associated with designing and creating the Florida Criminal Justice Workforce Research Information System: (1) to extract data from two transaction management information systems, which could then be used by researchers to describe and analyze the workforce that administers justice in Florida, (2) to pilot test the concept of developing a new research information source from existing data systems, (3) to forge partnerships with diverse criminal justice agencies having a mutual need to understand their respective workforces, (4) to design research files to enable internal and external researchers to utilize the data for analytical purposes, and (5) to describe the methodology used to create the workforce information system in sufficient detail to enable other states to replicate the process and develop their own criminal justice workforce research databases. The project was jointly conceived, designed, and completed by two state-level criminal justice agencies with diverse missions and responsibilities: the Florida Department of Law Enforcement (FDLE) and the Florida Department of Corrections (FDC). Data were extracted from two personnel management systems: the Automated Transaction Management System (ATMS) operated by the Florida Department of Law Enforcement, which contains data on all certified law enforcement, correctional, and correctional probation officers in Florida (Part 1), and the Cooperative Personnel Employment System (COPES) operated by the Department of Management Services, which contains data on all state employees (Part 2). Parts 3-5 consist of data extracted from Parts 1 and 2 regarding certification status (Part 3), education (Part 4), and training (Part 5). Two demographic variables, race and sex, are found in all parts. Parts 1 and 2 also contain variables on employment event type, employer type, position type, salary plan, job class, appointment status, and supervisor indicator. Part 3 variables are certification event type and certificate type. Part 4 variables include degree earned and area of degree. Part 5 includes a variable for passing or failing training certification.